(untitled) (Comparative & International Education Series, 2021)
Chapter 8|15 pages Assessing Acculturative Stress of International Students at a US Community College By Hardaye R. Hansen, Yuliya Shneyderman, Gloria S. McNamara, Lisa Grace Research shows that international college students experience high levels of acculturative stress, which can adversely impact their health and college success. The levels of immersion in one’s native culture and the culture of the U.S. may impact levels of acculturative stress in international students. This cross-sectional study examined community college international students. Immersion in a student’s native culture was positively associated with acculturative stress, while immersion in the U.S. culture was negatively associated with acculturative stress. Both students whose families moved to the United States and, as expected, students who spoke English as their first language experienced lower levels of acculturative stress. The results of the study imply that some international students may require more support in order to succeed in their college environment. Both students whose families moved to the United States and, as expected, students who spoke English as their first language experienced lower levels of acculturative stress.